2015
DOI: 10.3748/wjg.v21.i13.3893
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid phenethyl ester inhibits liver fibrosis in rats

Abstract: The protective effects of CAPE against liver fibrosis may be due to its ability to suppress the activation of HSCs by inhibiting oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…It was reported by others that Nrf2 protein levels are increased in dose-dependent manner of CAPE. [35][36][37] These hypotheses are confirmed by our data showing increased protein on Nrf2 in response to CS-induced oxidative stress in A549 cells.…”
Section: Discussionsupporting
confidence: 79%
“…It was reported by others that Nrf2 protein levels are increased in dose-dependent manner of CAPE. [35][36][37] These hypotheses are confirmed by our data showing increased protein on Nrf2 in response to CS-induced oxidative stress in A549 cells.…”
Section: Discussionsupporting
confidence: 79%
“…It has been shown that caffeic acid phenethyl ester (CAPE), which is an active component of the propolis agent, has antioxidant, antimicrobic, immunomodulator, antifibrotic, and antiinflammatory properties [16][17][18]. It is structurally similar to flavonoids and involves two annular structures, one of which carries two hydroxyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms of up‐regulatory effect of Nrf2 by ICAB require further investigation. Similarly, caffeic acid, a natural polyphenolic compound which has been widely accepted as a hepatoprotective folk medicine, also exerts its hepatoprotective effects by inhibiting the oxidative stress via Nrf2 pathway …”
Section: Discussionmentioning
confidence: 99%